1999
DOI: 10.1002/(sici)1097-0290(19990920)64:6<741::aid-bit14>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of chimeric antibody-producing CHO cells in the course of dihydrofolate reductase-mediated gene amplification and their stability in the absence of selective pressure

Abstract: Previously, the highest producing (HP) recombinant CHO subclones isolated at various methotrexate (MTX) levels showed different antibody production stability during long‐term culture, although they were clonally derived from CS13 transformant. In this study, genetic basis for their difference in antibody production stability was investigated using southern blot hybridization and fluorescence in situ hybridization (FISH) techniques. Southern analysis of HP subclones revealed that light‐chain (LC) and heavy‐chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 31 publications
(56 reference statements)
2
40
0
Order By: Relevance
“…This may be as a result of cell lines developing alternative resistance to MTX [41]. Despite clonal derivation using limited dilution cloning, cell populations can become quite heterogeneous in terms of growth rate and productivity following MTX amplification [41][42][43]. Therefore, it is likely that a cell population that was growing more quickly would become dominant during long-term culture, which may result in the higher growth rate and viable cell densities that were observed at the end of long-term culture [31].…”
Section: Discussionsupporting
confidence: 61%
“…This may be as a result of cell lines developing alternative resistance to MTX [41]. Despite clonal derivation using limited dilution cloning, cell populations can become quite heterogeneous in terms of growth rate and productivity following MTX amplification [41][42][43]. Therefore, it is likely that a cell population that was growing more quickly would become dominant during long-term culture, which may result in the higher growth rate and viable cell densities that were observed at the end of long-term culture [31].…”
Section: Discussionsupporting
confidence: 61%
“…However, over several rounds of amplifications, these high producers are prone to copy number loss, which introduces variability in productivity levels [5], [6]. The resulting productivity instability has been characterized by the combination of an imbalance in chromosome number, an absence of TTAGGG n sequence, the rearrangement of targeted genes to transcriptionally inactive sites and the methylation of promoters at CpG dinucleotides [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have indicated that the causes of production instability are either due to a loss of transgene copies (Fann et al, 2000;Kim et al, 1998;Strutzenberger et al, 1999), or a decrease in transcripts (Barnes et al, 2004;Kim et al, 1998), or both (Jun et al, 2006). Cytogenetic analyses indicated that the loss of gene copies might be due to chromosome instability caused by gene amplification (Derouazi et al, 2006;Kim and Lee, 1999). The underlying molecular mechanisms for the decrease in transcripts without loss of gene copy number have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%